Quality of Accounting System and Internal Control: How is the Implementation at PT. Nusantara Jaya Sentosa - Inta Budi Setya Nusa (Britain International for Academic Research (BIAR) Publisher, 2021)
This study aims to determine the quality of accounting information systems and internal controls at PT Nusantara Jaya Sentosa. The method used is descriptive qualitative. The data used are primary data and secondary data. Data analysis techniques are data reduction, data presentation and data verification. The results showed that the quality of PT Nusantara Jaya Sentosa's administrative system has changed from a manual system to a computerized system that produces useful output for each user of the information. This is evidenced by all the components needed to support a valid systems are owned by PT Nusantara Jaya Sentosa, and there is an element of internal control. The leadership of PT Nusantara Jaya Sentosa gave instructions that it was better to implement structured internal controls and develop access controls that were restricted by the use of a User and Password so that only specific units could perform internal access.